Medium-range Order in Al-based Metallic Glasses - Yi, Feng (My University, 2011)
Medium range order (MRO) is the structure order existing between the short range order and long range order in amorphous materials. Fluctuation electron microscopy (FEM) is an effective method to quantify MRO. The FEM signal depends on several effects. In this thesis, I will show how the probe coherence, sample thickness and energy filter affect the FEM signal. We have found that microalloying in Al-based glass has dramatic effect on the primary crystallization temperature and nanocrystal density after annealing treatment. FEM alone cannot uncover the details of MRO in these alloys. Therefore, I resort to modeling to solve the relationship between the variance signal and MRO structure. I improved Stratton and Voyles?s analytical model[1, 2]. I also did computer simulation. I explored the effects of thermal disorder and hydrostatic strain on the variance. The extracted size d and volume fraction ? in Al88Y7Fe5, Al88Y6Fe5Cu1 and Al87Y7Fe5Cu1 as-spun samples reveals the relationship between MRO in as-quenched sample and thermal behaviors in these alloys. I also did FEM experiments in relaxed Al88Y7Fe5 samples at various annealing times. MRO structure in these samples does not change. FEM was also done on Al87Y7Fe5Cu1 to check MRO variation during transient nucleation period. The extracted (d,?) based on combination of experimental data and simulation shows how MRO changes during this period.
Keywords: medium range order; fluctuation electron microscopy; metallic glass